2023
DOI: 10.1111/jop.13426
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity with proton therapy for oral and/or oropharyngeal cancers: A scoping review

Abstract: BackgroundOral and/or oropharyngeal cancers account for approximately 2% of all malignancies, with variation across age groups, genders, and geographic locations. Treatments for oral and/or oropharyngeal cancers usually consist of a combination of surgical excision most commonly followed by radiotherapy ± chemotherapy and/or immunotherapy/biotherapy depending on the nature of the malignancy. The significant morbidity caused by high‐dose radiotherapy to the head and neck region is widely observed. Proton therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…This rate was 45.8% with PT-based HNC chemoradiotherapy in the recent study by Gentile et al 3 It was found that dose (per Gy increase) to temporomandibular joints (TMJs) was associated with patient-reported RIT [Hazard ratio (HR): 1.14, p = 0.02], objective trismus (HR: 1.12, p = 0.04) and magnitude of decline in 2-year maximum interincisional opening ( p = 0.01). Interpreting Gentile's results together with those presented herein by Sethi et al 1 is of particular importance for the facts that (1) RIT is a common early-onset toxicity that also affects nearly half of all patients treated with PT; (2) it is mandatory to set dosevolume constraints for the masticatory apparatus components, including the TMJs, to avoid RIT in patients treated with PT; and (3) RIT is a devastating but underestimated complication in PT studies, as evidenced by the lack of emphasis on this complication in the 18 studies involved in this meta-analysis. Therefore, it is sensible to recommend the analysis of RIT in future PT research, which could aid in the development of preventative measures against it and its debilitating effects on the quality of life of the affected patient.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…This rate was 45.8% with PT-based HNC chemoradiotherapy in the recent study by Gentile et al 3 It was found that dose (per Gy increase) to temporomandibular joints (TMJs) was associated with patient-reported RIT [Hazard ratio (HR): 1.14, p = 0.02], objective trismus (HR: 1.12, p = 0.04) and magnitude of decline in 2-year maximum interincisional opening ( p = 0.01). Interpreting Gentile's results together with those presented herein by Sethi et al 1 is of particular importance for the facts that (1) RIT is a common early-onset toxicity that also affects nearly half of all patients treated with PT; (2) it is mandatory to set dosevolume constraints for the masticatory apparatus components, including the TMJs, to avoid RIT in patients treated with PT; and (3) RIT is a devastating but underestimated complication in PT studies, as evidenced by the lack of emphasis on this complication in the 18 studies involved in this meta-analysis. Therefore, it is sensible to recommend the analysis of RIT in future PT research, which could aid in the development of preventative measures against it and its debilitating effects on the quality of life of the affected patient.…”
supporting
confidence: 52%
“…Second, although the ORNJ has been presented as one of the acute PT toxicities by Sethi et al, 1 it is typically a late-onset complication of RT since it usually manifests after 6-months of RT in the absence of predisposing risk factors like previous mandibular surgery. Confirming this note, the median time to ORNJ development was 27 months (range: 2-127 months) in the study reported by Kubota and colleagues.…”
mentioning
confidence: 99%
“…Overall, the incidence ranges from 59% to 100%, with severe oral mucositis ranging from 23% to 81% [ 4 , 5 ]. While proton therapy has been associated with a reduction in severe oral mucositis by minimizing integral doses, the incidence of oral mucositis still ranges from 11% to 58% [ 6 , 7 ].…”
Section: Oral Mucositismentioning
confidence: 99%
“…The mucins found in saliva serve several important functions within the oral cavity. These functions include (1) making it less susceptible to abrasive trauma; (2) flushing the oral cavity to reduce debris and microorganisms; (3) dissolving tastants (see Taste Dysfunction section); (4) containing digestive enzymes; (5) neutralizing acids; (6) providing protection of the dentition (see Caries section); (7) containing proteins and peptides with antibacterial, antiviral, and antifungal effects; and (8) providing factors that enhance wound healing [35]. The parotid and submandibular glands contribute equally to about 90% of total daily saliva production, while the minor salivary glands supply the remaining amount.…”
Section: Salivary Gland Dysfunctionmentioning
confidence: 99%